O kwestii oryginału, przekładu autorskiego i adaptacji. Wokół polskiej i angielskiej wersji Antygony w Nowym Jorku Janusza Głowackiego - Amenta, Alessandro (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
Janusz Głowacki’s internationally acclaimed tragicomedy inspired by Sophocles’ Antigone has been the subject of intense debate and misinterpretations. The article aims to demonstrate that the play was primarily written in Polish, and that the English version is an adaptation/rewriting made by the author in collaboration with the American screenwriter Joan Torres. Furthermore, it shows that the English version was created while the writing of the Polish text was still in progress, so that the former influenced and left clear traces in the latter, questioning the traditional hierarchy between the original and the translated or adapted text.